2003
DOI: 10.1016/s0022-5223(03)01043-2
|View full text |Cite
|
Sign up to set email alerts
|

Perventricular device closure of muscular ventricular septal defects on the beating heart: technique and results

Abstract: Perventricular closure of multiple muscular ventricular septal defects is safe and effective. We believe that this could become the treatment of choice for any infant with muscular ventricular septal defects or any child with muscular ventricular septal defect and associated cardiac defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
0
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 12 publications
(18 reference statements)
3
160
0
10
Order By: Relevance
“…Previously, there were reports of intraoperative device closure of MVSD while patients were on cardiopulmonary bypass, but a perventricular approach through a median sternotomy could potentially avoid cardiopulmonary bypass, and such a hybrid approach could be used in babies and small infants. 447 In 2003, Bacha et al 448 described the technique and results of perventricular MVSD closure in 6 consecutive infants without cardiopulmonary bypass. Either a small median sternotomy or a subxiphoid minimally invasive incision was performed.…”
Section: Perventricular Device Closure Of Mvsdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, there were reports of intraoperative device closure of MVSD while patients were on cardiopulmonary bypass, but a perventricular approach through a median sternotomy could potentially avoid cardiopulmonary bypass, and such a hybrid approach could be used in babies and small infants. 447 In 2003, Bacha et al 448 described the technique and results of perventricular MVSD closure in 6 consecutive infants without cardiopulmonary bypass. Either a small median sternotomy or a subxiphoid minimally invasive incision was performed.…”
Section: Perventricular Device Closure Of Mvsdsmentioning
confidence: 99%
“…Korábban is születtek már beszámolók a muscularis kamrai septumdefektusok intraoperatív eszközös zárásáról cardiopulmonalis bypass mellett, de a medián sternotomián keresztül végzett perventricularis megközelítés segítségével esetleg elkerülhetővé válhat a cardiopulmonalis bypass használata, és ilyen hibrid megközelítés alkalmazható lehet újszülöttekben és kis csecsemőkben is. 447 2003-ban Bacha és munkatársai 448 hat egymást követő, cardiopulmonalis bypass alkalmazása nélkül elvégzett perventricularis muscularis kamrai septumdefektus zárása kapcsán leírták a módszer technikáját és eredményeit csecsemőkben. Kis medián sternotomiát vagy a kardnyúlvány alatt ejtett minimálisan invazív metszést alkalmaztak.…”
Section: Kamrai Septumdefektusokunclassified
“…In 2003, in a children's hospital in Chicago, Bacha et al reported on 6 children with muscular VSD who were successfully treated with transthoracic occlusion. Since then, many other articles have been published about the successful application of an Amplatzer occluder for muscular VSD using the transthoracic approach (Amin et al, 1998;Bacha et al, 2003;Cao et al, 2011;Zhang et al, 2012). In 2004, Amin et al achieved satisfactory outcomes by using a transthoracic approach for treating membranous VSD in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Первое сообщение о чрезвентрикулярном за-крытии ДМЖП на работающем сердце у животных под контролем эпикардиального ЭхоКГ представлено Z. Amin и соавт. [1] в 1998 г. Позднее данную методику применили у людей, однако показания ограничивались лишь мышеч-ными дефектами [2].…”
Section: Discussionunclassified